Evidence-Based Rehabilitation and Functional Recovery After Patellar Dislocation: Physical Therapy Assessment, Neuromuscular Re-education, and Return-to-Activity Outcomes - AlDossary, Khalaf Mohammed; Mohammad Rashed Almawash; Abdullah Aqeel Aati; Ahmed Jamman Alghamdi; Shaher Ibrahim Jebrer Sabei; Ghazi Jaber Huraysi; Mohammed Hamdan Al-Dosari; Abdulaziz Ibrahim Almathre; Abdullah Read Abdullah Alruaydan; Abdullah Saleh Alonazi; et al. (Saudi Journal of Medicine and Public Health, 2024)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Patellar dislocation is a significant knee injury affecting young, active individuals, often associated with pain, functional limitation, and high recurrence risk. Understanding its etiology, biomechanics, and management strategies is essential for optimizing outcomes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To review evidence-based rehabilitation and functional recovery strategies following patellar dislocation, emphasizing physical therapy assessment, neuromuscular re-education, and return-to-activity protocols. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature review and clinical synthesis were conducted, analyzing epidemiology, pathophysiology, diagnostic evaluation, and treatment modalities. Imaging techniques (radiographs, CT, MRI) and structured physiotherapy interventions were examined alongside surgical indications and procedures. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> First-time dislocations without osteochondral injury respond well to conservative care, including early mobilization, quadriceps and hip strengthening, proprioceptive retraining, and bracing. Recurrence rates range from 15–60%, influenced by anatomical risk factors such as trochlear dysplasia, patella alta, and increased TT–TG distance. Surgical intervention—MPFL reconstruction, tibial tubercle osteotomy, or trochleoplasty—is reserved for recurrent instability or structural abnormalities. Prognosis depends on adherence to rehabilitation and correction of biomechanical contributors. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Individualized management integrating early reduction, structured physiotherapy, and selective surgery is critical to restoring stability and preventing long-term patellofemoral morbidity. Interprofessional collaboration enhances diagnostic accuracy and rehabilitation success.